Emergence and spread of Tobacco streak virus menace in India and control strategies - Kumar, L.; Prasada Rao, R.D.; Reddy, A.S.; Madhavi, K.J.; Anitha, K.; Waliyar, Farid (2008)
Since the first outbreak of Tobacco streak virus (TSV), genus llarvirus as sunflower necrosis disease (SND) on sunflower and peanut stem necrosis disease (PSND) on groundnut in late 1990s, the virus has been a subject of much research in India. This review considers main features of TSV in India. The virus epidemics are very damaging to several crops in South India Natural accurrence of TSV was recorded on bottle gourd, chilli, crossandra, cotton, cowpea, cucumber, gherkin, ixora, marigold, mungbean, niger, okra, pumpkin, safflower, sesame, soybean, sunn hemp, urdbean, and several weed species. Coat protein gene sequence of TSV isolates from various locations and hosts are 97-100% identical. The virus is transmitted through pollen assisted by thrips (Thysanoptera: Thripidae) Epidemiological studies indicate TSV as a monocyclic disease in annual crops and asymptomatic weeds such as parthenium serve as TSV inoculum source. Attempts on identification and deployment of host resistance met with limited success. Phytosanitation and cultural methods of control were effective in reducing virus incidence but not popularly adopted by farmers. Major efforts are on-going to develop transgenic varieties using TSV coat protein gene. Additional research is required to determine the extent of TSV spread to other crops and its economic importance, understand disease epidemiology and development of host resistance for effective virus control, success of which will bring benefits to millions of farmers in India.